Dung Beetle Optimization algorithm for predicting damage to 2D truss structures - Lan, Hoang Ton-That (Smart Manufacturing Research Institute (SMRI), 2025)
This study predicts the degree of damage in 2D truss members using the Dung Beetle Optimization algorithm (DBO) in conjunction with finite element analysis for searching natural frequencies. The difference in these natural frequencies between the finite element model and actual measurements is known as the objective function. A number of scenarios, from simple to complex, are proposed to assess the performance of this algorithm. The convergence results, which are based on MATLAB software, required only 25~30 iterations and were then displayed to validate the potential practical use of DBO. Moreover, this short study only focused on the application of DBO to predict damage of truss structures, without going into the comparison of advantages and disadvantages with other existing algorithms.